2021
DOI: 10.1097/mpg.0000000000003265
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Endoscopy Quality Improvement Network Quality Standards and Indicators for Pediatric Endoscopists and Endoscopists in Training

Abstract: Introduction: High-quality pediatric endoscopy requires reliable performance of procedures by competent individual providers who consistently uphold all standards determined to assure optimal patient outcomes. Establishing consensus expectations for ongoing monitoring and assessment of individual pediatric endoscopists is a method for confirming the highest possible quality of care for such procedures worldwide. We aim to provide guidance to define and measure quality of endoscopic care for children. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…A strength of our study is that we evaluated a large number of children including preschoolers undergoing colonoscopy. Our rate of adequate bowel preparation was also higher than the ≥80% proposed by the PEnQuIN working group as a key indicator for high‐quality colonoscopic procedure (4). Another strength in this study is the objective confirmation of extent of procedure rather than just relying on the endoscopist’s report, in contrast to previous studies which have not reported on this.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A strength of our study is that we evaluated a large number of children including preschoolers undergoing colonoscopy. Our rate of adequate bowel preparation was also higher than the ≥80% proposed by the PEnQuIN working group as a key indicator for high‐quality colonoscopic procedure (4). Another strength in this study is the objective confirmation of extent of procedure rather than just relying on the endoscopist’s report, in contrast to previous studies which have not reported on this.…”
Section: Discussionmentioning
confidence: 62%
“…In recent years, attempts have been made to define quality indicators (QI) in pediatric colonoscopy (3). A joint North American and European initiative, Pediatric Endoscopic Quality Improvement Network (PEnQuIN), recommended ≥85% ileal intubation and ≥90% cecal intubation rates as quality standards in pediatric colonoscopy (4). Whether this is achievable in very young children, especially those aged less than 6 years, is unclear.…”
mentioning
confidence: 99%
“…A fourth domain included in the GRS, entitled “Training,” was determined to be outside the scope of this document, which applies to all facilities, regardless of the presence or absence of trainees. Standards and indicators that relate to training are included in an independent PEnQuIN consensus guideline that addresses endoscopist considerations, including training (25).…”
Section: Resultsmentioning
confidence: 99%
“…Standards and indicators that relate to training are included in an independent PEnQuIN consensus guideline that addresses endoscopist considerations, including training (25). Each standard that reached consensus for inclusion in this PEnQuIN guideline on facility quality is presented below, with the strength of recommendation and quality of supporting evidence (according to the GRADE approach), a short discussion of the evidence considered and the voting results.…”
Section: Resultsmentioning
confidence: 99%
“…A related benefit is the ability to ensure meeting of quality standards for colonoscopy. PEnQuIN has recommended that 90% cecal intubation rates and 85% terminal ileum intubation rates be maintained over time (11). As a group, we have consistently met these standards since inception of our data dashboard and will continue to monitor group performance to ensure maintained compliance with these standards.…”
Section: Discussionmentioning
confidence: 99%